Simultaneous Spectrophotometric Determination of Food Additives (Benzoic Acid, Caffeine, Aspartame and Acesulfame-K) in Cola Drinks by PLS Multivariate Calibration Method - Turak, Fatma; Ozgur, Mahmure Ustuen; Bozdogan, Abduerrezzak (SPRINGER, 2009)
Aspartame (Apt), Acesulfame-K (Ace-K) low-calorie, high-potency artificial sweeteners are currently used in beverages and dietary food and drinks. Their increased application in food and drink products has given a new impetus to develop fast and accurate methods for their determination. Absorption spectra of Asp, Caf, Ace-K and BA strongly overlap. Therefore a direct determination of these analytes in quaternary mixture is impossible without a separation step. In order to overcome this difficulty partial least squares (PLS) method has been proposed. A spectrophotometric method for the routine, rapid end simultaneous determination of Ace-K, Caf, Aspt and BA in cola drinks was investigated. A calibration set containing between 3-5 mu g mL(-1) of Ace-K, Caf, and BA, 5-7 mu g mL(-1) of Aspt was used. The method involves the use of 27 standard mixtures of the four compounds assayed, considered at three concentration levels and measured of samples in a 0.1 N H3PO4. The designed and optimized training set of-calibration was applied to the determination of four food additives in several synthetic mixtures. Three commercial cola drinks (coca-cola, pepsi-cola, cola-turka) that contained the four additives were also satisfactorily analyzed without separation step.
Keywords: Cola drinks; food additives; spectrophotometry; sweeteners; Biochemistry & Molecular Biology; Chemistry